Phylogeography of New Zealand's coastal benthos - P. M. Ross; I. D. Hogg; C. A. Pilditch; C. J. Lundquist (New Zealand Journal of Marine and Freshwater Research, 2009)
During the past 30 years, 42 molecular studies have been undertaken in New Zealand to examine the phylogeography of coastal benthic invertebrates and plants. Here, we identify generalities and/or patterns that have emerged from this research and consider the processes implicated in generating genetic structure within populations. Studies have used various molecular markers and examined taxonomic groups with a range of life histories and dispersal strategies. Genetic disjunctions have been identified at multiple locations, with the most frequently observed division occurring between northern and southern populations at the top of the South Island. Although upwelling has been implicated as a cause of this disjunction, oceanographic evidence is lacking and alternative hypotheses exist. A significant negative correlation between larval duration and genetic differentiation ( r 2 = 0.39, P 0.001, n = 29) across all studies suggests that larval duration might be used as a proxy for dispersal potential. However, among taxa with short larval durations (